Efeito de bordadura nas extremidades de parcelas de milho irrigado - SILVA, PAULO SERGIO LIMA E; Gilson de Souza, Pedro; Gilson de Souza, Pedro; Edson Montenegro, Elvis; Edson Montenegro, Elvis (Revista Ceres, 2015)
.